“We Closed the Ports to Protect Refugees.” Hygienic Borders and Deterrence Humanitarianism during Covid-19 - Tazzioli, Martina; Stierl, Maurice (International political sociology, 2021)
This article investigates how the security-humanitarian rationale that underpins migration governmentality has been restructured by and inflected in light of hygienic-sanitary borders which enforce racialised confinement in the name of both migrants' and citizens' safety from infection by Covid-19. Focusing on the politics of migration containment along EUrope's frontiers, examining in particular border reinforcements carried out by Italy, Malta and Greece, we interrogate how the pandemic has been exploited to enact deterrence through hygienic-sanitary border enforcements. These enforcements are underpinned by an ambivalent security-humanitarian narrative that crafts migrants as subjects who cannot be protected by EU member states from the pandemic if allowed inside, and, at once, as potential vehicles of contagion - ‘Corona spreaders’ - and thus as dangers on a bacterial-hygienic level. Our article demonstrates that these EUropean border measures are more than temporary responses to an unprecedented health crisis. Rather, the pandemic has been seized as an opportunity to strengthen existing deterrence measures and hamper migrants' access to asylum through biopolitical and spatial tactics that aim to restructure the border regime. While emphasising the historical trajectories and continuities underwriting these current developments, we contend that the pandemic functions as an accelerator of dynamics of migrant incarceration and containment.